Implementasi Kebijakan Kurikulum Merdeka Di Sd Negeri Tingkir Lor 2 Kota Salatiga - Siah, Ina; YSH, AY Soegeng; Egar, Ngasbun (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
The aims of this research are (1) to determine communication regarding the implementation of the Merdeka Curriculum policy, (2) to determine the resources for implementing the Merdeka Curriculum, (3) to determine the disposition of the implementation of the Merdeka Curriculum, and (4) to determine the bureaucratic structure of implementing the Merdeka Curriculum. The research approach used is a qualitative descriptive approach using Edward III's 1980 policy theory. Data collection techniques are through observation, interviews and documentation. The validity data of the test using source triangulation, technique and time triangulation. The data analysis techniques using data reduction and categorization, data presentation and conclusions. The research results show first, communication regarding the implementation of the Merdeka Curriculum has been achieved. Second, supporting school resources have not been achieved because human resource and information resource indicators have not been met. Another reason there are still teachers who lack of the ability to compose teaching modules. Beside that, when carrying out the initial assessment, the teacher has not yet analyzed the results of the initial assessment. Third, the disposition in implementing the Merdeka Curriculum shows that the honesty indicators have not been met. The teacher did not conduct initial assessment analysis during the two school years.The last , Standard Operating Procedures are not made by the school, but they are only conveyed by the school principal through meetings. Based on the results of the research that has been carried out, the Education Department should supervise and assist the implementation of the Merdeka Curriculum programmatically in order to find out the obstacles faced in implementing of the Merdeka Curriculum at schools. The Department also needs to increase human resource competency regarding the Merdeka Curriculum. For schools, it is best to increase human resource competency. Mentoring and supervision at school also needs to be carried out by the school principal so that he can find out information resources and teacher honesty in implementing the Curriculum. A Standard Operating Procedure also needs to be created to serve as a guide for teachers in implementing the Curriculum at schools. For educators, teachers should increase competence regarding the implementation of the Curriculum and increase honesty in carrying out learning preparation and learning assessment.